ChemInform Abstract: Mechanism of the Kumada—Corriu Cross‐Coupling Catalyzed by Low‐Coordinate Bis(amido)‐Nickel Complexes: Identification of Nickel(I)—(III) Catalytic Intermediates. Issue 48 (2nd December 2014) - Vedernikov, Andrei N.
Abstract Review: 11 refs.